Digilantism, discrimination, and punitive attitudes: a digital vigilantism model - Galleguillos, Sebastián (Crime, media, culture, 2022)
In this article, I propose and apply a digital vigilantism model to a specific incident that occurred in Mexico, where the death of two innocent people was filmed through Facebook Live. Using a mixed methods approach and content analysis, I analyzed digilante Facebook posts (N = 942) coding gender, digital vigilantism categories, discriminatory comments, and punitive attitudes aimed at the perpetrators and the inciter of the lynching. The categories include investigating, blaming, or rebuking, while the discriminatory comments include classism, racism, homophobia, and body-shaming. I coded the punitive attitudes distinguishing four categories: non-physical punishment (calling for God’s wrath and the guilty conscience of the targets), legal sanction, death, and other punishment. The findings reveal the key role gender played in digilantism: females tend to conduct more investigations and low level attacks (blaming) than males, but males tend to perpetrate more harsh attacks (rebuking) than females. The most popular punitive attitude is calling for the death of targets, revealing tensions between legal sanctions and digilantes’ desired punishment. This study suggests the presence of different expressions of discrimination and reasons to engage in digilantism, encompassing both legal and illegal behavior deployed in a mainstream social media platform such as Facebook.